Local delivery of soluble fractalkine (CX3CL1) peptide restores ribbon synapses after noise-induced cochlear synaptopathy - Manickam, Vijayprakash; Maity, Sibaprasad; Murali, Sree Varshini; Gawande, Dinesh Y.; Stothert, Andrew R.; Batalkina, Lyudamila; Cardona, Astrid E.; Kaur, Tejbeer (Frontiers in Cellular Neuroscience, 2024)
Efficacy of different isoforms of chemokine fractalkine was evaluated for restoration of loss of inner hair cell ribbon synapses and hearing after noise-induced cochlear synaptopathy (NICS). Previously, we have demonstrated a critical role for the fractalkine signaling axis (CX3CL1-CX3CR1) in synaptic repair, wherein noisedamaged ribbon synapses are spontaneously repaired in the presence of fractalkine receptor (CX3CR1) expressed by cochlear macrophages. Here, we examined whether local administration of fractalkine ligand (CX3CL1 or FKN) in the form of a peptide is effective in restoring synapses and hearing loss after NICS. A single transtympanic injection of soluble isoform of FKN (sFKN) peptide at 1 day after synaptopathic noise trauma for 2 hours at 93 decibel sound pressure level led to significant recovery of auditory brainstem response (ABR) thresholds, ABR peak I amplitudes and ribbon synapses in FKN knockout mice when compared to mice injected with full length membrane-bound FKN peptide (mFKN). Likewise, local treatment with sFKN peptide in FKN wild type mice restored synaptopathic noise-damaged ribbon synapses and ABR peak I amplitudes. Mechanistically, FKN regulates macrophage numbers in the damaged cochlea and in the absence of macrophages, sFKN failed to restore loss of synapses and hearing after NICS. Furthermore, sFKN treatment attenuated cochlear inflammation after NICS without altering the expression of CX3CR1. Finally, injected sFKN peptide was detectable inside the cochlea for 24 hours localized to the basilar membrane and spiral lamina near the sensory epithelium. These data provide a proof-of-principle that local delivery of an immune factor, sFKN is effective in restoring ribbon synapses and hearing loss after NICS in a macrophage-dependent manner and highlights the potential of sFKN as an immunotherapy for cochlear synaptopathy due to noise.Summary: Transtympanic delivery of soluble FKN peptide is effective in restoring inner hair cell ribbon synapses and hearing after noise-induced cochlear synaptopathy in a macrophage-dependent manner.